2019
DOI: 10.1002/cphc.201900347
|View full text |Cite
|
Sign up to set email alerts
|

On‐Surface Synthesis of Porous Carbon Nanoribbons on Silver: Reaction Kinetics and the Influence of the Surface Structure

Abstract: We report on the influence of the surface structure and the reaction kinetics in the bottom‐up fabrication of porous nanoribbons on silver surfaces using low‐temperature scanning tunneling microscopy. The porous carbon nanoribbons are fabricated by the polymerization of 1,3,5‐tris(3‐bromophenyl)benzene directly on the Ag surface using an Ullmann‐type reaction in combination with dehydrogenative coupling reactions. We demonstrate the successful on‐surface synthesis of porous nanoribbons on Ag(111) and Ag(100) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…The proposed chemical structure of this pore-containing dimer is shown in the inset of Figure f, which depicts a covalent product generated by a double C–C bond coupling. The DFT simulated STM image (Figure h) and previous results support our deduction of the molecular structure. For convenience in the statements below, we indicate the C–C connection forming a pore-containing dimer as “D” type, in contrast to the “S” type forky dimer from the single C–C covalent bond formation (Figure g,h).…”
Section: Resultssupporting
confidence: 89%
“…The proposed chemical structure of this pore-containing dimer is shown in the inset of Figure f, which depicts a covalent product generated by a double C–C bond coupling. The DFT simulated STM image (Figure h) and previous results support our deduction of the molecular structure. For convenience in the statements below, we indicate the C–C connection forming a pore-containing dimer as “D” type, in contrast to the “S” type forky dimer from the single C–C covalent bond formation (Figure g,h).…”
Section: Resultssupporting
confidence: 89%
“…In practice, this problem can be quite challenging when many isomers of a given tecton have to be considered and experimentally probed. Moreover, when some of these building blocks are additionally able to adopt multiple adsorbed conformations, for example mirror image forms, predicting structure formation in such systems can be very difficult [26,27] . An useful tool which can facilitate these efforts has been the theoretical modeling, enabling easy modification of the parameters characterizing molecular tectons.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experimental studies have shown that a careful choice of halogenated aryl monomers results in the formation of polymers, and first their precursors, with predefined structural properties. In this case, by tuning molecular shape, size, and position of reactive centers (halogens) in the backbone, it has been possible to direct the metal–organic self-assembly and further polymerization toward diverse adsorbed architectures. However, in the case of more complex monomers, with many possible halogen positions, this task can be quite challenging. For these building blocks, a small change in the position of a halogen(s) can have a significant impact on the morphology of the resulting polymer. For that reason, experimental testing of a series of potential building blocks is necessary, aiming at the selection of the optimal one.…”
Section: Introductionmentioning
confidence: 99%